Analysis of the Impact of Short Circuit Faults in Converter Valve Submodules on Valve Power Transmission - Yirun Ji; Qian Yuan; Chengjie Zhou; Minxiang Yang; Xuanfei Huang; Libo Ma; Hongshan Zhao (Energies)
Faults of a Modular Multilevel Converter (MMC)-type converter valve significantly impact the reliability of flexible DC transmission systems. This paper analyzed the impact of ongoing short circuit faults in submodules on the power transmission of the MMC-type converter valve of which redundant submodules had been depleted. First, MMC’s working principle and its submodules’ possible operational states were investigated. Then, fault mechanisms for intra-submodule Insulated-Gate Bipolar transistor (IGBT) short circuits and inter-submodule short circuits were modeled to infer changes in power transmission during submodule faults. To quantify the impact of submodule faults on the energy transfer efficiency of the converter valve, an energy transfer efficiency index was proposed to obtain analytical expressions for energy transfer efficiency in the case of intra-submodule and inter-submodule short-circuit faults. Finally, the effectiveness of the proposed analytical model was verified through Simulink simulations. Simulation results indicate that ongoing intra-submodule and inter-submodule short circuits increase the input power of the converter valve, reducing energy transfer efficiency. Moreover, the energy transfer efficiency continues to decline with an increase in faulty submodules.